Correlation between emotional regulation and peripheral lymphocyte counts in colorectal cancer patients - Kakoo Brioso,Estela; Ferreira Cristina,Sérgio; Costa,Luis; Ouakinin,Silvia (PeerJ, 2020)
Background Colorectal cancer is one of the most common cancers worldwide. Psychological morbidity has an important impact on quality of life and major clinical outcomes. Several data have shown that the immune system may be a key player on the relation between psychological features and cancer outcomes. Natural Killer (NK) cells have been shown to be influenced by psychological factors. The aim of this investigation was to assess the impact of anxiety, depression, and anger state, trait, and expression on the immune response, particularly, their effect on NK cells and CD8+ T cells in surgical colorectal cancer patients. Methods We studied 54 surgical colorectal cancer patients and assessed patients pre-surgically, post-surgically, and 12 months after surgery (follow-up). We applied the Hospital Anxiety and Depression Scale and the State-Trait Anger Expression Inventory and measured peripheral T cells, CD8+ T cells, and NK cells. We did a cross-sectional analysis as well as a longitudinal assessment of the variables during the follow-up period. Results Pre-surgical assessment: Trait anger, angry reaction, and anger-out had a significant negative correlation with NK cells. The lymphocytes values were unaffected by the presence of clinical anxiety or depression. Post-surgical assessment: Patients without clinical anxiety had higher levels of T cells. Angry reaction was negatively correlated with NK cells. Lymphocytes values were unaffected by the presence of clinical depression. Follow-up assessment: Patients without clinical depression had higher T cell counts. Trait anger and angry reaction were negatively correlated with the levels of NK cells. The lymphocytes values were unaffected by the presence of clinical anxiety. Longitudinal assessment: Angry-temperament, anger expression, and anger-in reduced significantly from the first to the second assessment. Anxiety, state anger, and trait anger significantly diminished from the pre-surgical to the follow-up assessment. Depression levels did not alter during the follow-up period. The lymphocyte count, and particularly T cells and CD8+ T cells, was significantly higher in the follow-up when compared with the pre-surgical assessment. Conclusion Our study suggests the existence of a relation between psychological response and immune response in colorectal cancer patients. We identified the importance of emotional regulation as a potential modulator for NK cell counts. Higher values of propensity to experience anger states and express them outwards seem to be associated with lower NK cell counts.
Keywords: Colorectal cancer; NK cells; Anger; Depression; Anxiety; Immune system; T Cells